The Effect of Teacher Recruitment and Retention on Teacher Performance at Islamic Boarding Schools in Kamang Magek - Rita Amelia Alimin; Junaidi Junaidi (Institut Agama Islam Sunan Giri Ponorogo, 2026)
This study was motivated by the importance of human resource management in improving the quality of education at Islamic boarding schools, particularly through the recruitment and retention of educators, which influence teacher performance. Issues identified in Islamic boarding schools in Kamang Magek Subdistrict include recruitment that is not yet fully professional and competency-based, low welfare, unclear employment status, and limited career development for educators. This study aims to analyze the influence of educator recruitment and retention on teacher performance. The study employs a quantitative approach using a correlational method. Recruitment variables are measured through planning, methods, selection, objectivity, and alignment with values, while retention variables include job satisfaction, welfare, career development, and work culture. Teacher performance is measured through teaching ability, discipline, character building, involvement in boarding school activities, adherence to institutional values, and interpersonal communication. This study is expected to provide theoretical and practical contributions to the development of human resource management in Islamic boarding schools to improve the quality of teacher performance and education.